Arahan Pemanfaatan Ruang Pesisir Berbasis Bahaya Tsunami di Kecamatan Cisolok Kabupaten Sukabumi - Asti Dwi Lestari; Lilis Sri Mulyawati; Mujio Mujio (Jurnal Zona, 2025)
Cisolok Subdistrict is a coastal area that directly faces the Indian Ocean and lies within a tsunami-prone zone due to megathrust fault activity off the southern coast of West Java. The varied morphology of the region, ranging from steep hills to flat lowlands, increases its level of vulnerability. According to the worst-case tsunami scenario from BMKG, a megathrust earthquake with a magnitude of 8.7 has the potential to trigger a tsunami that would directly impact this region. This research aims to formulate spatial utilization directives based on tsunami hazard levels. The approach applied in this study includes spatial analysis using Geographic Information Systems (GIS) and qualitative descriptive analysis through literature reviews and the collection of both primary and secondary data. The analysis results are classified into five hazard categories: very low, low, medium, high, and very high. Spatial utilization directives are developed based on these hazard levels, taking into account land use data and the Regional Spatial Plan (RDTR) of the Palabuhanratu Area. In zones with high and very high hazard levels, land use is directed toward supporting mitigation efforts, such as green open spaces, evacuation routes, protection zones, and disaster infrastructure. Dense functions such as residential, commercial, services, and tourism are restricted or redirected to safer zones. In medium hazard zones, limited development is permitted under specific technical requirements for disaster-resistant buildings and evacuation systems. Meanwhile, areas with low to very low hazard levels offer greater development flexibility, provided that disaster mitigation principles are still observed